Numbers and narratives: Developing a mixed-methods approach to understand mobility in later life. (November 2016) - Meijering, Louise; Weitkamp, Gerd
Abstract: The aim of this methods-focused article is to explore the potential benefits of integrating GPS, diary and in-depth interview data to gain richer insights into the everyday mobility practices of older adults. Eighteen adults, aged 65–90 years, living in the Netherlands, participated in the study. Our findings illustrate how quantitative (GPS) and qualitative (interviews and diary-based) approaches together can generate different insights and layers of understanding from each individual method in order to enhance the overall study findings. Our findings demonstrate that our methodological approach generates new insights with respect to GPS-measured and self-reported mobility, time-geographies, and micro-geographies of older adults in the Netherlands. In conclusion, our mixed-methods approach contributes to a better understanding of the everyday mobility practices of older adults, and could be used in other demographic groups. Highlights: Our mixed-methods approach increases understanding of mobility of older adults. The approach combined GPS-tracking, travel diaries and in-depth interviews. GPS-data and self-reported data generate new insights in mobility geographies. Our mixed-methods approach enables multi-layered understanding of time-geographies. Our mixed-methods approach enables multi-layered understanding of micro-geographies.